Trace Elements and Minerals in Health and Longevity (Cham : Springer International Publishing, 2018)
This book describes the role of trace elements in health and longevity, pursuing a biogerontological approach. It offers essential information on the impact of trace elements on molecular and physiological processes of aging, and on their impact on health in connection with aging. The major topics covered in its 11 chapters, each dedicated to a specific trace element or mineral, are: a) Role of the element in species longevity, b) Recommended intake for longevity in animal species and in the elderly, c) Deficiency and age-related disease, d) Excess/toxicity and age-related disease, and e) Interactions with drugs prescribed in the elderly. Clinical, animal and other laboratory models of interest in aging are included, which enable a more in-depth analysis to be made. The respective chapters are a mixture of overviews and more in-depth reviews in which the mechanisms of aging are described from the point of view of their specific interactions with trace elements and minerals .
1. Preface -- Iron -- Copper -- Selenium -- Zinc -- Cobalt -- Chromium -- Boron -- Molybdenum -- Sodium -- Magnesium -- Iodine -- Fluoride -- Potassium -- Manganese -- Calcium -- Index.
Biomedical and Life Sciences
text file PDF
Keywords: Medicine; Cell physiology; Geriatrics; Developmental biology